Understanding the Vicious Cycle: Relationships between Nonconsensual Sexting Behaviours and Cyberbullying Perpetration - Yunhao Hu; Elizabeth Mary Clancy; Bianca Klettke (Sexes, 2023)
With the increased ubiquity of digital technology, sexting behaviours, defined as the online sending, receiving, or disseminating of sexually explicit messages, images, or videos, have become increasingly frequent, particularly among young adults. While prior research found sexting behaviours to be associated with cyberbullying behaviours, the role of consent as part of this association has been largely unexplored. The current study investigates whether the relationship between sexting behaviours and cyberbullying perpetration might be explained by a subset of nonconsensual sexting behaviours, such as engagement in nonconsensual sext dissemination and sext-hassling. A large convenience sample of young Western cisgendered adults (n = 1688, M age = 23.15, SD = 3.23, 52.7% women) completed an anonymous online survey exploring harmful online behaviours (nonconsensual sext dissemination, sext-hassling, cyberbullying victimisation/perpetration). A hierarchical logistic regression was used to analyse predictive relationships between variables. The results showed no significant association between consensual sext-sending and cyberbullying perpetration in young adults. However, nonconsensual sexting behaviours, particularly sext-hassling and nonconsensual sext dissemination, were predictive of cyberbullying perpetration. Finally, cyberbullying victimization appeared to be the most strongly associated factor with cyberbullying perpetration. These findings suggest that future research and prevention efforts surrounding sexting and cyberbullying perpetration would benefit from a focus on consent and the bidirectional nature of cyberbullying behaviours.